Stanley, flat again! - Brown, Jeff, 1926-; Nash, Scott, 1959- (New York : HarperCollins Publishers, 2003)
After Stanley Lambchop goes flat once again, he uses his flatness to help win a sailboat race and to rescue a classmate from a collapsed building.
480
Accelerated Reader AR
Maine illustrator. Scott Nash lives on Peaks Island off the coast of Maine.
Keywords: Sailing -- Fiction; Humorous fiction